Intensified Impact of Winter Arctic Oscillation on Simultaneous Precipitation Over the Mid–High Latitudes of Asia Since the Early 2000s - Zhou, Haibo; Fan, Ke (Frontiers in Earth Science, 2021)
This study reveals an intensified impact of winter (November–February mean) Arctic Oscillation (AO) on simultaneous precipitation over the mid–high latitudes of Asia (MHA) since the early 2000s. The unstable relationship may be related to the changes in the tropospheric AO mode and the subtropical jet. Further analyses suggest that their changes may be attributable to the interdecadal changes in the stratospheric polar vortex. During 2002–2017, the anomalously weak stratospheric polar vortex is accompanied by intensified upward-propagating tropospheric planetary-scale waves anomalies. Subsequently, the stratospheric geopotential height anomalies over the North Atlantic high-latitudes propagate downward strongly, causing the changes in the tropospheric AO mode, that is, the positive height anomalies over the North Atlantic high-latitudes are stronger and extend southward, corresponding to the stronger and eastward extension of negative height anomalies over the North Atlantic mid-latitudes. Thus, the Rossby wave source anomalies over Baffin Bay and the Black Sea are strong, and correspondingly so too are their subsequently excited the Rossby waves anomalies. Meanwhile, the planetary-scale waves anomalies propagate weakly along the low-latitude waveguide, causing the intensified and southward shift of the subtropical jet. Therefore, the strong Rossby waves anomalies propagate eastward to the MHA. By contrast, during 1979–1999, the strong stratospheric polar vortex anomaly is accompanied by weak upward-propagating planetary-scale waves anomalies, resulting in weaker height anomalies over the North Atlantic mid–high latitudes. Consequently, the anomalous Rossby waves are weak. In addition, the subtropical jet weakens and shifts northward, which causes the Rossby waves anomalies to dominate over the North Atlantic, and thereby the impact of winter AO on simultaneous precipitation over the MHA is weak.